Communicating about the Middle East respiratory syndrome outbreak to the international community and in-country foreigners, Republic of Korea, 2015 - Lee, Minwon; Sohn, Jooyoung; Park, Kidong (Western Pacific Surveillance and Response, 2016)
Under the International Health Regulations (2005), risk communication is one of eight core capacities that WHO Member States need to detect and respond to public health threats.1 During the recent MERS outbreak in the Republic of Korea,2,3 the Ministry of Health and Welfare (MOHW) made continued efforts for risk communication with the international community.The Republic of Korea receives a large number of international visitors and also has a large migrant population. In 2014 there were 14 million foreign visitors and 1.8 million foreigners residing in the country (3.6% of the total population) 4. Due to this, the government provided information on the MERS outbreak targeted at both international travellers and foreigners residents, the latter as foreigners are likely to be poorly informed of infection risk and response guidelines due to language barriers. Information was provided by the MOHW through multiple channels including the existing English website of MOHW (english.mw.go.kr) , a newly created MERS portal website (www.mers.go.kr) and a newly created multi-language free telephone hotline. The MERS portal was established to communicate accurate and timely information on MERS to the public in Korean and English. The hotline was also established to provide information about the MERS in Korean, English, Chinese, Japanese, Vietnamese, Mongolian, Arabic and Russian.This report analyses the performance of multi-language communication effort on MERS provided by the MOHW.